2006
DOI: 10.1089/jop.2006.22.41
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Myopia Progression with 0.05% Atropine Solution

Abstract: The results of this study demonstrate that, with regular instillation, topical 0.05% atropine is an effective agent for controlling myopia progression in a majority of school-aged children for at least a period of 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 15 publications
4
52
0
2
Order By: Relevance
“…Fan and colleagues (2007), who investigated the effect of 1% atropine ointment on myopia progression in children over a one year period, demonstrated that the rate of myopia progression was lower in children receiving atropine than in those using the placebo. A similar conclusion was also drawn by Lee et al (2006), Polling et al (2016) and Fang et al (2010) who evaluated the effectiveness of 0.5% and 0.025% atropine for slowing the development of myopia in Asian and Caucasian children after one year (Table 1.7.6.2).…”
Section: The Autonomic Innervation Of the Choroidsupporting
confidence: 76%
“…Fan and colleagues (2007), who investigated the effect of 1% atropine ointment on myopia progression in children over a one year period, demonstrated that the rate of myopia progression was lower in children receiving atropine than in those using the placebo. A similar conclusion was also drawn by Lee et al (2006), Polling et al (2016) and Fang et al (2010) who evaluated the effectiveness of 0.5% and 0.025% atropine for slowing the development of myopia in Asian and Caucasian children after one year (Table 1.7.6.2).…”
Section: The Autonomic Innervation Of the Choroidsupporting
confidence: 76%
“…22,23 The mechanism of action of atropine in myopia is suspected to include reduction of neuronal activity and increase in the general release of retinal neurotransmitters. 20 It has also been proven that pirenzepine and himbacine inhibit myopia in a dose-dependent manner, suggesting that these drugs mediate their effects via a receptoral mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Because CNVs of different genes are related to many phenotypes, we identified CNVs of genes encoding mAChRs in an effort to determine a possible correlation with high myopia in the present study. Form-deprived myopic (FDM) animals were used to study the expression levels of mAChRs in myopic eyes before and after atropine treatment.…”
Section: -10mentioning
confidence: 99%
“…Indeed, the Atropine Treatment of Myopia 2 (ATOM2) study and related studies offer enticing evidence that doses as low as 0.01% atropine can quite effectively slow myopia progression in children with very low levels of pupil dilation, photophobia, cycloplegia, and allergy. [10][11][12] The findings from ATOM2 in particular have encouraged clinicians to consider lowdose atropine therapy, although there are difficulties in prescribing such doses as they are not easily available. The Cochrane group further suggests that corneal reshaping or orthokeratology and bifocal soft contact lenses are promising treatments, although still in need of more randomized controlled clinical trials.…”
mentioning
confidence: 99%